Microscopic and molecular detection of Haemoproteus spp in wild and domestic pigeons, Iraq - Salah M. Sabri; Maulood M.Shather (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Haemoproteus spp. is the most common blood parasite in birds, which identified in several geographical areas, worldwide causing variable health impacts. Aim:This study was conducted to investigate Haemoproteus spp. in wild and domestic pigeons and the effect of sex and months on the infection rate by traditional methods. Also, it aims to identify the genetic diversity of Haemoproteus spp. targeting the Cytochrome b gene. Materials and methods:A total of 180 pigeons; 90 wild and 90 domestic, were selected and subjected to collection of blood that examined microscopically; and then, the positive sampleswere testedfurthermore molecularly by the nested PCR. Phylogenetic analysis was conductedin some positive PCR products. Results:Microscopic examination of 180 stained blood smears revealed that 18.89% of study pigeons were infected with Haemoproteusincluding 15% wild and 3.89% domestic pigeons. Within mature erythrocytes, pigmented gametocytes of Haemoproteus were appeared markedly as black or violet small granules, free in cytoplasm and extend along the nuclei of erythrocytes. Relation to months, the total results were increased significantly in October and December but decreased in February. Concerning to sex of study animals, the total results showed that females having a higher rate of infection than males. However, no significant variation was seen between the results of male and female pigeons in both wild and domestic birds. Conclusion: The prevalence of Haemoproteus spp. in wild pigeon was higher than domestic pigeon, with presence a significant association between infection, month and sex of study animals. The results of nested PCR assay were greatly supported the obtained findings of microscopy, suggesting that molecular assays can be applied directly to identify the prevalence of Haemoproteus genus and its species among different birds. Moreover studies in other Iraqi localities and birds are necessary to estimate the prevalence rate of parasitic infections.